41 years into the bronchial tree: a very obstructive cap. (18th February 2016) - Pellissier, Aude; Kebdani, Samira; Lacheheb, Mohamed; Lainez, Ségolène; Froudarakis, Marios E.; Vergnon, Jean‐Michel
Abstract: Inhaled foreign body, which remains unknown from the childhood until the mid‐age is extremely rare. We report the case of a 58‐year‐old man who was addressed to our department to remove a pen cap, inhaled forty‐one years earlier. It was discovered during a routine pre‐op check‐up for bronchiectasis, caused by the long period of retention into the bronchial tree. The successful removal of the cap changed completely the therapeutic strategy, as there was no indication for surgical resection any more.